Anisotropic and size-dependent mechanical responses of free-standing Ni-Nb metallic glass thin film. (June 2021) - Wang, N.; Cao, Q.P.; Yao, W.; Wang, X.D.; Zhang, D.X.; Fecht, H.-J.; Jiang, J.Z.
Abstract: Via in-situ tensile test, we demonstrated a brittle-to-ductile transition of Ni-Nb metallic glass (MG) thin films when the film thickness decreased from 363 nm to 87 nm. The elastic strain limit of 4.7% and apparent work hardening behavior were seen for free-standing 87 nm-thick film. Contrary to quenched MGs, anisotropic mechanical response existed in MG thin films with nanocolumnar structure owing to the deteriorated bonding strength of column boundaries. Graphical abstract: Image, graphical abstract